A dual-aptamer-based biosensor for specific detection of breast cancer biomarker HER2 via flower-like nanozymes and DNA nanostructures. Issue 23 (15th May 2019) - Ou, Dan; Sun, Duanping; Lin, Xiangan; Liang, Zhixian; Zhong, Yongsheng; Chen, Zuanguang
Abstract : A dual-aptamer electrochemical biosensor based on flower-like nanozymes and DNA nanostructures was fabricated for detection of breast cancer biomarker HER2. Abstract : Developing highly sensitive and selective detection strategies for biomarkers is beneficial for fundamental research and disease diagnosis. Herein, we constructed a sandwich-type electrochemical aptasensor to detect the breast cancer cell biomarker Human Epidermal Growth Factor Receptor 2 (HER2). The aptasensor was a combination of tetrahedral DNA nanostructures (TDNs)–aptamer as recognition probes and flower-like nanozymes/horseradish peroxidase (HRP) as signal nanoprobes. In the process of assembling the biosensor, the TDN–aptamer 1 as a bio-recognition element was immobilized on the gold electrode (GE) surface for capturing the biomarker HER2. The nanozyme Mn3 O4 was decorated by Pd@Pt nanozymes which were linked by the aptamer 2 and natural enzyme HRP. The designed Mn3 O4 /Pd@Pt/HRP nanoprobe (nanoprobe 1) was used to amplify the biosensor signal via catalyzing the oxidation of hydroquinone (HQ) with hydrogen peroxide (H2 O2 ). After binding HER2, an aptamer–protein–nanoprobe sandwich system was fabricated on the GE surface. Lastly, a Pd@Pt/HRP/complementary DNA (cDNA) nanoprobe (nanoprobe 2) was added on the surface of nanoprobe 1 through DNA hybridization of aptamer 2 and cDNA to form a dendritic DNA nanostructure to further amplify the signal significantly. The results indicate that the aptasensor shows a broad linear response from 0.1 to 100.0 ng mL −1 and the low detection limit is 0.08 ng mL −1 . The designed approach holds great potential for the construction of various aptasensors for the effective and convenient detection of different biomarkers.